Modeling Waste Generation in the Gayamsari Sub-district Service Trade Area with a Spatial Approach - Orzhe Elantry Faiz; Maryono Maryono (Universitas Sultan Ageng Tirtayasa, 2024)
Based on the Semarang City Regulation No.5 of 2004 concerning the Semarang City Spatial Plan 2000-2010 Article 11, Gayamsari Sub-district is included in BWK V, which is an area with the center of trade, office, and residential activities that contribute greatly to the increase in waste generation in Semarang City every year. The existence of this waste problem requires a study in the form of an identification study related to waste generation consisting of characteristics, volume, and composition of waste visualized through spatial modeling. In this study, waste generation was measured in 30 sample shops in the trade and service area of Gayamsari Subdistrict, then the analysis used was Descriptive Statistical analysis, GIS analysis, and Moran's I analysis. The research results generated from the implementation of this research are waste generation data in the form of total weight of waste generation, weight per type of waste, average weight of waste, and type of waste composition, through spatial analysis resulting in mapping the location of sample stores, the level of waste, and the range of neighborhoods around the store, and through Moran's I analysis resulting in the identification of spatial autocorrelation between sample stores, the form of spatial patterns, and hotspot maps of waste generation distribution. The resulting research results are used to draw conclusions on the application of the non-residential urban area waste measurement method in SNI 19-3964-1994.